Estoques de C e N em frações da matéria orgânica do solo sob sistemas silvipastoris e pastagem na Amazônia Oriental - Oliveira, Hugo Mariano Rodrigues de (Universidade Federal do Tocantins, 2019)
Soil quality assessment can be performed using several variables, but those that most identify changes caused by changes in soil use are those related to soil organic matter (MOS). In this sense, the objective of this work was to evaluate the impacts of the conversion of native forest to agricultural use in the region of the Eastern Amazon in the state of Tocantins in Eutrophic Red Argissolo. Five areas with different land use and management were used, considering the treatments: silvipastoral system with 30% (SSP30%); and 60% shading (SSP60%); native forest (MN); degraded pasture area (MD); intensive pasture management system with mombaça grass (MI). Soil samples at depths 0-5, 5-15, 15-30, 30-60 and 60-100 cm were used for granulometric fractionation of MO and subsequent determination of C and N of the soil and estimated the stocks in the fractions of MO. It was also carried out an analysis of the natural abundance of the 13C isotope and the determination of the lability of the MO fractions, which later allowed to calculate values of carbon management index (CMI). The SSP60%, provided an improvement in soil quality, because it presented higher C and N content in the particle size fraction of organic matter. The SSP30% provided the largest stocks of C and N in the soil, but provided a decrease in soil quality, due to lower LC levels and a decrease in the C stock of particulate organic matter (POM). In spite of being the system with the lowest C and N input and lower C lability, the IM provided the highest values of C and N content in the POM fraction, being equal to the SSP60%, which may represent a future improvement in quality of the soil. The values of δ13C show that the conversion of MN to SSP60% did not promote changes in the composition of the 13C isotope, with a higher participation of C3 plants in this system. The SSP30% due to higher anthropogenic action showed a higher contribution of C from the C4 plant. On the other hand, the MD had a greater proportion of C of C3 plants than the MI.